A cooperative control strategy for power quality based on parallel grid-connected converters - LIANG Xiaorui; LUO Yuhang; ZHANG Huaying; TU Chunming; LIU Huicong; ZHENG Yuting (电力工程技术)
Power quality control based on grid-connected converter can effectively utilize the surplus capacity of the converter and improves the benefits. However, existing methods tend to only consider grid-following (GFL) control and fail to fully utilize the control potential of multiple converters. In this paper, a cooperative control strategy for harmonic compensation and voltage drop suppression is proposed based on a parallel system of GFL and grid-forming (GFM) converters. Firstly, the basic control principle and mathematical model of grid-connected converter are introduced. Secondly, to compensate the harmonics at the point of common coupling (PCC), a harmonic sub-compensation method is proposed. This approach can improve the flexibility of harmonic compensation and reasonably apportion harmonic between grid-connected converter of different capacities. To support the PCC voltage, the parallel system can operate in three conditions: normal operation condition, condition of GFL support voltage independently and co-supported operating condition. Through compensation capacity calculation and reactive power allocation, the voltage at the PCC can maintain near the rated voltage. Finally, the feasibility and superiority of the proposed strategy are verified through simulations.